Endoscopic transnasal management of inverted papilloma involving frontal sinuses - Gotlib, Tomasz (Termedia Publishing House, 2012)
Inverted papilloma is a benign locally aggressive tumor of paranasal sinuses which has been traditionally managed with external surgical approaches. Advances in tumor imaging, surgical instrumentation and intraoperative visualization have led to a gradual shift to endonasal attachment-oriented surgery. Involvement of both frontal sinuses by inverted papilloma is rare. There are scant reports in the literature regarding this topic. We present 2 cases of the tumor involving both frontal sinuses removed by median drainage (Draf III procedure) under endoscopic guidance without any additional external approach. The whole cavity of both frontal sinuses was easily inspected at the end of the procedure. No early or late complications were observed. No recurrence was seen in 1-year or 2-year follow-up. Management of frontal sinus inverted papilloma with the endoscopic median drainage approach is feasible and seems to be effective.